Analysis Of Students' Problem-Solving Abilities Open-Ended Type Problems In Class XI IPA SMAN 1 Kota Solok - Ade Syafrinaldo; Suherman Suherman (JETL (Journal of Education, Teaching and Learning), 2025)
The purpose of this study is to reveal whether students' problem-solving abilities have changed in solving problems, especially Open-ended problems . The application of Open-ended type questions is used as an effort to train students' problem-solving abilities in mathematics learning. This study is a combination of descriptive research and Pre-experiment with a one group pre-test-post-test design . The conclusions of this study are 1) The problem-solving abilities of class XI IPA 5 students of SMAN 1 Kota Solok who have been trained using Open-ended type problem-solving ability questions in learning, have changed towards the better compared to before. 2) The application of learning using Open-ended questions helps students to play an active role during learning activities because it can help students be more open in developing various answers in solving problems